Life History and Mating Behavior of Rhagoletis solanophaga (Diptera: Tephritidae), a Non-Diapausing Species with Highly Variable Mating Duration - Rull Gabayet, Juan Antonio (2016)
As an initial contribution to understanding the adaptive value of behavioral and life-history strategies, the life cycle and mating behavior of an unstudied species of tephritid fruit fly in the genus Rhagoletis are characterized for the first time. Over a 9-month fruiting period, a small proportion of Solanum appendiculatum Dunal (< 10 %) was found to be infested with a single larva of Rhagoletis solanophaga (Hernández & Frías). The average duration of R. solanophaga lifecycle (c.a. 140 days from egg laying to death of adults) exceeded the three month fruitless period. Additionally, R. solanophaga is capable of exploiting Solanaceous plants in at least two genera. These features could have selected for a non-diapausing species of Rhagoletis, a genus where most species are univoltine. Nevertheless, some individuals in the population became dormant. As other members of the genus, R. solanophaga exhibited a resource defense mating system with forced copulations and multiple mating. Both males and females could be highly promiscuous and individual mating success exhibited a wide range of outcomes. Regardless of mating success, mated females stored similar amounts of sperm in two spherical spermathecae. Long copulations were observed, perhaps functioning as a form of mate guarding with probable disadvantages for females. We outline hypotheses and opportunities for future comparative studies examining sperm competition and mate guarding.